2019
DOI: 10.1192/bjp.2019.59
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial comparing narrative exposure therapy with present-centred therapy for older patients with post-traumatic stress disorder

Abstract: BackgroundEvidence-based treatment and age-specific services are required to address the needs of trauma-affected older populations. Narrative exposure therapy (NET) may present an appropriate treatment approach for this population since it provides prolonged exposure in a lifespan perspective. As yet, however, no trial on this intervention has been conducted with older adults from Western Europe.AimsExamining the efficacy of NET in a sample of older adults.MethodOut-patients with post-traumatic stress disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 49 publications
2
23
0
1
Order By: Relevance
“…All four PTSD clusters showed significant reduction of symptoms, whereas intrusions, arousal and reactivity decreased more slowly than symptoms of avoidance, cognition and mood. These results are in line with other controlled NET studies in vulnerable patients, such as children and adolescents, 52 patients with borderline personality, 17 the elderly, 53 refugees 15 and asylum-seeking refugees with PTSD and depressive disorder. 54 Of the 23 participants, 11 (48%) were in remission for PTSD at follow-up.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All four PTSD clusters showed significant reduction of symptoms, whereas intrusions, arousal and reactivity decreased more slowly than symptoms of avoidance, cognition and mood. These results are in line with other controlled NET studies in vulnerable patients, such as children and adolescents, 52 patients with borderline personality, 17 the elderly, 53 refugees 15 and asylum-seeking refugees with PTSD and depressive disorder. 54 Of the 23 participants, 11 (48%) were in remission for PTSD at follow-up.…”
Section: Discussionsupporting
confidence: 91%
“…Until now, most NET studies excluded patients with psychosis, bipolar disorder, substance misuse and suicidal ideations. 17,[52][53][54] One case study reported positive results of NET in a refugee with PTSD and psychotic features. 57 Mørkved et al 55 compared NET and prolonged exposure therapy for PTSD and argued that NET and prolonged exposure have several commonalities when it comes to the principles of exposure.…”
Section: Main Findingsmentioning
confidence: 99%
“…In two thirds of studies the risk of bias was medium to low (Table 5; Ertl et al, 2011;Hijazi et al, 2014;Lely et al, 2019a;Morath et al, 2014a;Morath et al, 2014;Neuner et al, 2008;Neuner et al, 2004b;Orang et al, 2018;Stenmark et al, 2013;Zang et al, 2014Zang et al, , 2013, while in a third of studies the risk of bias was found to be unclear or medium to high (Adenauer et al, 2011(Adenauer et al, , 2015Bichescu et al, 2007;Crombach & Siehl, 2018;Hensel-Dittmann et al, 2011;Neuner et al, 2010;Pabst et al, 2014;Schaal et al, 2009). The complete ratings can be found in Suppl.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Hence, “stabilization” not only included training in affect regulation and self-calming abilities but also focused on trauma-related contents and clearing of associations between traumatic experiences and present symptomatology or difficulties in everyday life. The present-centered therapy approach introduced by Schnurr et al (60) includes similar contents and was shown to be an efficacious and safe treatment for trauma-related disorders (64, 65). Skipping the presented aspects and starting directly with confrontational methods, e.g.…”
Section: Discussionmentioning
confidence: 99%